Immune response and reactogenicity after immunization with two-doses of an experimental COVID-19 vaccine (CVnCOV) followed by a third-fourth shot with a standard mRNA vaccine (BNT162b2): RescueVacs multicenter cohort study. (September 2022) - Ascaso-del-Rio, Ana; García-Pérez, Javier; Pérez-Olmeda, Mayte; Arana-Arri, Eunate; Vergara, Itziar; Pérez-Ingidua, Carla; Bermejo, Mercedes; Castillo de la Osa, María; Imaz-Ayo, Natale; Riaño Fernández, Ioana; Astasio González, Oliver; Díez-Fuertes, Francisco; et al.
Summary: Background: There is no evidence to date on immunogenic response among individuals who participated in clinical trials of COVID-19 experimental vaccines redirected to standard national vaccination regimens. Methods: This multicentre, prospective controlled cohort study included subjects who received a COVID-19 experimental vaccine (CVnCoV)(test group, TG) - and unvaccinated subjects (control group, CG), selected among individuals to be vaccinated according to the Spanish vaccination program. All study subjects received BNT162b2 as a standard national vaccination schedule, except 8 (from CG) who received mRNA-1273 and were excluded from immunogenicity analyses. Anti-RBD antibodies level and neutralising titres (NT50) against G614, Beta, Mu, Delta and Omicron variants were analysed. Reactogenicity was also assessed. Findings: 130 participants (TG:92; CG:38) completed standard vaccination. In TG, median (IQR) of anti-RBD antibodies after first BNT162b2 dose were 10740·0 BAU/mL (4466·0-12500) compared to 29·8 BAU/mL (14·5-47·8) in CG ( p <0·0001). Median NT50 (IQR) of G614 was 2674·0 (1865·0-3997·0) in TG and 63·0 (16·0-123·1) in CG ( p <0·0001). After second BNT162b2 dose, anti-RBD levels increased to ≥12500 BAU/mL (11625·0-12500) in TG compared to 1859·0 BAU/mL (915·4-3820·0) in CG ( p <0·0001). NT50 was 2626·5 (1756·0-5472·0) and 850·4 (525·1-1608·0), respectively ( p <0·0001). Variant-specific (Beta, Mu, Omicron) response was also assessed. Most frequent adverse reactions were headache, myalgia, and local pain. No severe AEs were reported. Interpretation: Heterologous BNT162b2 as third and fourth doses in previously suboptimal immunized individuals elicit stronger immune response than that obtained with two doses of BNT162b2. This apparent benefit was also observed in variant-specific response. No safety concerns arose. Funding: Partly funded by the Institute of Health Carlos-III and COVID-19 Fund, co-financed by the European Regional Development Fund (FEDER) "A way to make Europe".